Non-Invasive Ventilation in Immunocompromised Patients with Respiratory Failure - Giammatteo, Valentina; Bisanti, Alessandra; Montini, Luca; Bello, Giuseppe; Antonelli, Massimo (Seminars in Respiratory and Critical Care Medicine, 2025)
Non-invasive ventilation (NIV) is commonly recommended as respiratory support for selected immunocompromised patients with acute respiratory failure (ARF), offering an alternative to tracheal intubation, which historically carried high mortality rates in this population. Initial enthusiasm for NIV stemmed from its potential to avoid invasive ventilation. However, evolving evidence has demonstrated a gradual reduction in mortality among intubated immunocompromised patients, attributed to advances in oncologic therapies, improvements in intensive care unit (ICU) management, and refined triage criteria. These findings have led to a reassessment of NIV's role in this context, suggesting that immunocompromised patients with ARF may benefit from treatment strategies similar to those used in the general population, including timely intubation when clinically indicated. Notably, survival outcomes remain influenced by inconsistent intubation criteria across studies, underlying causes of immunosuppression, and patient severity. Recent studies also highlight poor ICU outcomes in patients with specific oncohematologic profiles and fragile physical states, tempering enthusiasm for invasive support in these subgroups. Identifying predictors of NIV failure is critical to guide ventilation strategies in immunocompromised patients with ARF and determine when ongoing non-invasive support may become counterproductive. However, since there are no validated tools to predict the success or failure of NIV in these patients, careful bedside assessment of their response to non-invasive strategies is essential to ensure timely intubation and prevent dangerous delays in those who do not show signs of improvement. After the widespread adoption of NIV, the introduction of high-flow nasal cannula oxygenation has emerged as a new tool in managing specific scenarios of respiratory failure, playing a central role in influencing the prognosis of critically ill patients. Its effectiveness has also been investigated in immunocompromised patients.
Keywords: non-invasive ventilation; acute respiratory failure; hematological malignancies; immunocompromission; outcomes